Multi-domain optical network virtual technology based on SDN - Shidong LIU; Pan WANG (Dianxin kexue)
With the development of information society，the information flow in the network began to grow rapidly，optical network requires not only large capacity and long distance transmission，but also the need for dynamic and flexible controls，the traditional automatic switching optical network architecture is very difficult to meet it. At the same time，storage access to massive amounts of data is a very high requirement for the scalability of the distributed storage architecture. A resource balancing strategy based on SDN for the inter-domain optical network virtualization service was proposed. Simulation results indicate that network resources can be allocated effectively，service acceptance ratio is improved，and network blocking probability is reduced.